2019
DOI: 10.1155/2019/3041262
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Inhibition by LY411575 Attenuates Osteoblast Differentiation and Decreased Ectopic Bone Formation Capacity of Human Skeletal (Mesenchymal) Stem Cells

Abstract: Background. Chemical biology approaches using small molecule inhibitors targeting specific signaling pathways are useful tools to dissect the molecular mechanisms governing stem cell differentiation and for their possible use in therapeutic interventions. Methods. Stem cell signaling small molecule library functional screen was performed employing human bone marrow skeletal (mesenchymal) stem cells (hBMSCs). Alkaline phosphatase (ALP) activity and formation of mineralized matrix visualized by Alizarin red stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Small molecule inhibitors targeting intracellular signaling pathways have been employed as chemical tools to determine the molecular mechanisms controlling stem cell proliferation and differentiation 25,30 . Our group has employed this chemical biology approach to identify a number of molecular targets and pathways that are www.nature.com/scientificreports/ www.nature.com/scientificreports/ important for osteoblast and adipocyte differentiation of hMSCs 25,[27][28][29]31,34,35 . In the current study, we identified XAV-939 small molecule inhibitor, during small molecule library functional screen, as an enhancer of osteoblast differentiation of hMSCs 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small molecule inhibitors targeting intracellular signaling pathways have been employed as chemical tools to determine the molecular mechanisms controlling stem cell proliferation and differentiation 25,30 . Our group has employed this chemical biology approach to identify a number of molecular targets and pathways that are www.nature.com/scientificreports/ www.nature.com/scientificreports/ important for osteoblast and adipocyte differentiation of hMSCs 25,[27][28][29]31,34,35 . In the current study, we identified XAV-939 small molecule inhibitor, during small molecule library functional screen, as an enhancer of osteoblast differentiation of hMSCs 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Human skeletal (mesenchymal) stem cells (hMSCs) are multipotent stem cells that have the potential to proliferate and differentiate into various cell types including bone-forming osteoblasts 23 , 24 . The osteoblastic differentiation of hMSCs involves various signaling pathways including Tankyrase 4 , JAK-STAT signaling 25 , Wnt/β-catenin 26 , TGFβ 27 , Notch signaling 28 , and Hedgehog signaling 29 . However, the relative contribution of these signaling pathways on osteoblastic differentiation remained to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Ethical approval for all animal experiments was obtained from the Animal Care Committee of King Saud University. In vivo experiments were performed as previously described [19]. In brief, cells were trypsinized to a single-cell suspension and resuspended in culture medium with/without the small molecule inhibitor, BMS-833923.…”
Section: Methodsmentioning
confidence: 99%
“…The role played by Notch in both osteoclastogenesis, as well as osteoblast differentiation, remains controversial due to discrepancy in the results obtained by several studies due to the experimental design, cell source, and operating conditions [ 311 , 313 , 314 , 315 ].…”
Section: The Tgf-β Superfamilymentioning
confidence: 99%